2021
DOI: 10.21203/rs.3.rs-605964/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementation of An Organizational Intervention To Improve Low-Wage Workers' Safety, Health And Wellbeing: Findings From The Workplace Organizational Health Study

Abstract: Background: Many organizational interventions aim to improve working conditions to promote and protect worker safety, health, and well-being. The Workplace Organizational Health Study used process evaluation to examine factors influencing implementation of an organizational intervention. This paper examines the extent to which the intervention was implemented as planned, the dose of intervention implemented, and ways the organizational context hindered or facilitated the implementation of the intervention.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Second, the Implementation Guidelines-organized into four stages of an integrated approach-provided a process to plan the intervention using strategies to change working conditions. The planning process culminated in a 13-month intervention implemented at both leadership and site levels to change our three working conditions (safety and ergonomics, work intensity, and job enrichment), as described in detail elsewhere [26].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, the Implementation Guidelines-organized into four stages of an integrated approach-provided a process to plan the intervention using strategies to change working conditions. The planning process culminated in a 13-month intervention implemented at both leadership and site levels to change our three working conditions (safety and ergonomics, work intensity, and job enrichment), as described in detail elsewhere [26].…”
Section: Discussionmentioning
confidence: 99%
“…We designed the intervention for sites to assess working conditions, develop action plans, and implement changes for three working conditions over the course of 13 months. However, another recent study reported that it may take worksites approximately nine months to form an integrated team and craft a TWH action plan with on-going technical assistance [63], suggesting we may have been too ambitious in our intervention timeline [26]. We also realize the intervention development process, design, and choice of key characteristics may look different for organizations that are creating an intervention for one site verses tailoring the intervention for multiple sites.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
See 3 more Smart Citations